2007
DOI: 10.2135/cropsci2006.06.0374
|View full text |Cite
|
Sign up to set email alerts
|

GGE Biplot vs. AMMI Analysis of Genotype‐by‐Environment Data

Abstract: The use of genotype main effect (G) plus genotype‐by‐environment (GE) interaction (G+GE) biplot analysis by plant breeders and other agricultural researchers has increased dramatically during the past 5 yr for analyzing multi‐environment trial (MET) data. Recently, however, its legitimacy was questioned by a proponent of Additive Main Effect and Multiplicative Interaction (AMMI) analysis. The objectives of this review are: (i) to compare GGE biplot analysis and AMMI analysis on three aspects of genotype‐by‐env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
1,209
3
58

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,100 publications
(1,438 citation statements)
references
References 49 publications
(103 reference statements)
35
1,209
3
58
Order By: Relevance
“…However, the AMMI has seldom been used together with the GGE Biplot in studies on sugarcane. Other crops, for example, wheat (Kaya et al 2006, Yan et al 2007), soybean (Asfaw et al 2009), sorghum (Rao et al 2011), and carrot were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the AMMI has seldom been used together with the GGE Biplot in studies on sugarcane. Other crops, for example, wheat (Kaya et al 2006, Yan et al 2007), soybean (Asfaw et al 2009), sorghum (Rao et al 2011), and carrot were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Há vários estudos comparando os métodos AMMI e GGE Biplot, e em alguns há evidências da superioridade da metodologia GGE Biplot e outros da AMMI (Yan et al, 2000;Gauch, 2006;Gauch et al, 2008;Yan et al, 2007;Asfaw et al, 2009;Namorato et al, 2009).…”
Section: Introductionunclassified
“…Blanche & Myers (2006) used the GGE Biplot method to identify test locations that optimize genotype selection on the basis of their discriminating ability and representativeness. Yan et al (2007) compared GGE Biplot and AMMI analyses. They concluded that both GGE Biplot and AMMI analyses combined rather than separated G and GxE in mega-environment analysis and genotype evaluation.…”
Section: Introductionmentioning
confidence: 99%